Some characteristics of poplar saplings (1/1) in experimental nurseries of Golestan province - GHolamali Gholami; Ali Reza Modir Rahmati; Raf'atollah Ghasemi (تحقیقات جنگل و صنوبر ایران, 2010)
The project of investigation on characteristics of poplar saplings (1/1) was carried out to select the best poplar clones in Chalaki research nursery of Golestan province during 2001 to 2004. For this purpose, 4 clones of Native poplars were collected from different areas of the province and planted beside 31 exotic clones provided from research center of Alborz Karaj. In the first year‚ cuttings were prepared from all clones and planted in 20 cm spacing within rows with 1.3m distance. Parameters including survival rate, diameter and height growth of saplings were recorded. Analysis of variance and Duncan multiple range test were applied using SAS software. Results indicated significant statistical differences between studied poplar clones. Populus deltoids and P. euramericana showed higher diameter and height growth compared to the other clones.